استفتاء اقليم كوردستان 2017 ومستقبل العلاقة مع الحكومة الاتحادية - احمد محمد, فيان; ثامر جواد, شيماء; عارب صادق, سيروان (Journal of College of Education, 2020)
Such as the referendum an opportunity to demand independence, and achieve the goal that is struggling for the Kurds for years, but the results of the referendum was contrary to what was expected as things returned to before 2014, where the federal government re-control of the areas that withdrew from them in 2014, Has increased its demand to transfer the management of regional airports to the central government as well as border crossings in the region to be under the supervision of the federal government, and after extensive negotiations between the parties, the government of the region seeks through the negotiations with Baghdad to obtain some privileges and powers under the sovereignty of Iraq.